Pheromone receptor of the globally invasive quarantine pest of the palm tree, the red palm weevil (Rhynchophorus ferrugineus). Issue 9 (22nd March 2021) - Antony, Binu; Johny, Jibin; Montagné, Nicolas; Jacquin‐Joly, Emmanuelle; Capoduro, Rémi; Cali, Khasim; Persaud, Krishna; Al‐Saleh, Mohammed Ali; Pain, Arnab
Abstract: Palm trees are of immense economic, sociocultural, touristic, and patrimonial significance all over the world, and date palm‐related knowledge, traditions, and practices are now included in UNESCOs list of the Intangible Cultural Heritage of Humanity. Of all the pests that infest these trees, the red palm weevil (RPW), Rhynchophorus ferrugineus (Olivier), is its primary enemy. The RPW is a category‐1 quarantine insect pest that causes enormous economic losses in palm tree cultivation worldwide. The RPW synchronizes mass gathering on the palm tree for feeding and mating, regulated by a male‐produced pheromone composed of two methyl‐branched compounds, (4 RS, 5 RS )‐4‐methylnonan‐5‐ol (ferrugineol) and 4( RS )‐methylnonan‐5‐one (ferrugineone). Despite the importance of odorant detection in long‐range orientation towards palm trees, palm colonization, and mating, the pheromone receptor has not been identified in this species. In this study, we report the identification and characterization of the first RPW pheromone receptor, RferOR1 . Using gene silencing and functional expression in Drosophila olfactory receptor neurons, we demonstrate that RferOR1 is tuned to ferrugineol and ferrugineone and binds five other structurally related molecules. We reveal the lifetime expression of RferOR1, which correlates with adult mating success irrespective of age, a factor that could explain the wide distribution and spread of this pest. As palm weevils are challenging to control based on conventional methods, elucidation of the mechanisms of pheromone detection opens new routes for mating disruption and the early detection of this pest via the development of pheromone receptor‐based biosensors.